Crowdsourcing, Outsourcing to Obtain a Creativity Group - Jacques Digout; Marwan Azouri; Jean-Marc Decaudin; Stephane Rochard (Arab Economic and Business Journal, 2013)
Crowdsourcing is a concept that first appeared in an article written by Jeff Howe in 2006 in the Wired Magazine in which the author illustrates the emerging phenomena of the outsourcing of various activities by companies to an undefined generally large group of people on the Internet in the form of an open call. Although this process has long been limited to the computing sector, it currently tends to cater a wider number of sectors. Firms using this process are always more numerous in order to outsource, for limited financial compensations, activities that cannot be completed by their own employees or considered too costly in terms of manpower, finances and time. This paper aims at defining, through concrete examples, how Crowdsourcing directly impact on the variables of the mix-marketing such as product development, price positioning, distribution and communication but also people, process and physical evidence. At last, the article focuses on the potential evolution of the Crowdsourcing in the coming years.
Keywords: 650; Web 2.0; Internet users; Crowdsourcing; Marketing network; plateform; crowd; Open Source; User Innovation; Open Innovation; Dellideastorm; Quirky; MyStarbucksIdea; Jeff Howe